2001
DOI: 10.1034/j.1600-0420.2001.079001049.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of a neurosurgical two‐wall orbital decompression in the treatment of severe thyroid associated ophthalmopathy

Abstract: ABSTRACT.Purpose: Follow-up of patients with severe thyroid associated ophthalmopathy treated with a transcranial two-wall orbital decompression and reconstruction. Conclusion:The transcranial two-wall decompression is a simple, an efficient and a low-risk procedure for treatment of patients with severe thyroid associated ophthalmopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Linnet et al used a transcranial approach for the lateral orbital wall and orbital roof via bicoronal skin incision in a group of 30 patients (50 orbits) with DON and exophthalmos 55. The median exophthalmos reduction achieved was 4.0 mm (0–10 mm), and the visual acuity improved in 28 of 32 affected eyes with normalisation in 19 eyes.…”
Section: Resultsmentioning
confidence: 99%
“…Linnet et al used a transcranial approach for the lateral orbital wall and orbital roof via bicoronal skin incision in a group of 30 patients (50 orbits) with DON and exophthalmos 55. The median exophthalmos reduction achieved was 4.0 mm (0–10 mm), and the visual acuity improved in 28 of 32 affected eyes with normalisation in 19 eyes.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple anatomical surfaces (medial, floor, and lateral wall) could be used with or without intraconal fat debulking. 1,15,16,[18][19][20][21][22][23][24][25]27 These anatomical areas can be approached through various surgical incisions, including endonasal. 28 Surgery should always be individualized to the patient's specific needs, and in cases where there is a choice of surgeries, the least invasive approach should be selected to reduce complications (which can include death, stroke, intracranial injury, vision loss, numbness, and paresthesia.)…”
Section: Commentmentioning
confidence: 99%
“…9 Postoperative newonset symptomatic diplopia may occur in 0% to 70% of cases, depending on surgical approach and the amount of retrodisplacement of the globe. 18,[21][22][23][24]26,[31][32][33] In a recent study, 33 we found that patients who developed newonset primary or downgaze diplopia after deep lateralwall decompression achieved a greater decrease in proptosis (6 mm vs 3.1 mm) as compared with patients with no new-onset diplopia.…”
Section: Commentmentioning
confidence: 99%
“…It is destructive in nature with a risk of many complications such as vision loss, motility disturbance of extraocular muscles, cerebrospinal fluid leakage, obstructive sinus disease, eyelid malposition, infraorbital nerve disturbance, and dacryostenosis. Although series published so far suggest that decompression surgery benefits TAO patients at least in the short term, 6–12 studies of its long‐term effects with a reasonable number of patients are scarce 13–16 …”
Section: Introductionmentioning
confidence: 99%